Understanding Procrastination Among Prospective Teachers in Public-Sector Universities: A Phenomenological Study - Mustafa, Zainab; Muneer, Munib Ul; Usman, Zarmina (Journal of Development and Social Sciences, 2025)
The purpose of this study was to investigate the experiences of procrastination among aspiring educators at Pakistani public universities in Lahore. Future teachers who procrastinate run serious risks to their academic performance and readiness for the workforce. Little is known about how cultural, institutional, and emotional factors interact to influence procrastination behaviors in developing nations, despite a wealth of research conducted in Western contexts. Six teacher-educators chosen by purposive sampling and eighteen aspiring teachers participated in in-depth interviews using a qualitative phenomenological design. Interpretative phenomenological analysis was used to analyze the data thematically. The results showed that emotional difficulties, ambiguous academic frameworks, peer normalization, technological distractions, and individual time management shortcomings all have an impact on procrastination. According to the participants, institutional impediments, emotional distress, and ingrained behaviors all contribute to long-term delays. In order to encourage proactive learning behaviors and professional development among aspiring teachers, it is recommended that teacher education programs incorporate training in emotional regulation, structured academic support, digital literacy development, and peer culture shifts.